Comparative research of Non-Profit Organisations: A preliminary assessment - Marybel Perez; Georg von Schnurbein; Theresa Gehringer (University of Basel, Center for Philanthropy Studies (CEPS), 2016)
This article examines the state of comparative research of Non-Profit Organisations (NPOs). Reviewing 110 articles published in philanthropic and third sector journals in the last 10 years, this article surveys the essential aspects of the research design and content of comparative studies. It is found that practical constraints of the comparative research practice influence NPO research. It is observed that volunteering, regulation NPOs development and philanthropy are the main subject areas examined in comparative research of NPOs, and the main analytical frameworks adopted are social capital, civil society, and welfare regimes. The conclusion points to the necessity to improve the comparative research agenda through the development multi-level analyses, the inclusion of the time dimension and the assessment of the sets of theories used.
Keywords: 330